Physicochemical and Sensory Evaluation of Romanian Monofloral Honeys from Different Supply Chains - Elena Daniela Bratosin; Delia Mirela Tit; Manuela Bianca Pasca; Anamaria Lavinia Purza; Gabriela Bungau; Ruxandra Cristina Marin; Andrei Flavius Radu; Daniela Gitea (Foods)
Honey quality and authenticity are influenced by floral origin, processing, and storage, with implications for composition and sensory appeal. This study offers a comparative assessment of eight monofloral honey samples, representing five botanical varieties: acacia, linden, rapeseed, lavender, and thyme. For acacia, linden, and rapeseed, both producer-sourced and commercial honeys were analyzed, while lavender and thyme samples were available only from local beekeepers. The botanical origin of each sample was confirmed using morphological markers of pollen grains. Physicochemical characterization included acidity, pH, moisture content, refractive index, hydroxymethyl furfural (HMF), proline concentration, and carbohydrate profiling by HPLC-RID. Acacia honey exhibited the lowest acidity and HMF levels, alongside the highest fructose/glucose (F/G) ratios, indicating superior freshness, lower crystallization risk, and a sweeter flavor profile. In contrast, rapeseed honey showed elevated glucose levels and the lowest F/G ratio, confirming its tendency to crystallize rapidly. All samples recorded proline concentrations well above the quality threshold (180 mg/kg), supporting their authenticity and proper maturation. The estimated glycemic index (eGI) varied between 43.91 and 62.68 and was strongly inversely correlated with the F/G ratio (r = −0.98, p < 0.001). Sensory evaluation highlighted acacia honey from producers as the most appreciated across visual, tactile, and flavor attributes. Correlation analyses further revealed consistent links between sugar composition and both physical and sensory properties. Overall, the findings reinforce the value of integrated analytical and sensory profiling in assessing honey quality and authenticity.